Reproductive phenology of two co-occurring Neotropical mountain grasslands - Le Stradic, Soizig [UNESP]; Buisson, Elise; Fernandes, Geraldo W.; Morellato, Leonor P. C. [UNESP] (Wiley, 2018)
Aim: Climate tends to explain phenological variations in tropical ecosystems. However, water availability and nutrient content in soil strongly affect plant communities, especially those on old, climatically buffered, infertile landscapes (OCBILs), and may impact these ecosystems’ plant reproductive phenology over time. Here, we compare the reproductive phenology of sandy and stony tropical grasslands, two co-occurring herbaceous communities of the campo rupestreOCBILs. We asked whether flowering, fruiting and dispersal are seasonal in both grasslands, and whether these phenophases differ due to variations in soil properties. We also asked whether the phenological strategies and the number of flowers and fruits differ between these two grasslands as soil conditions vary. Location: Serra do Cipó, Minas Gerais, Brazil. Methods: The phenology of herbaceous species of sandy and stony grasslands was monitored monthly over two consecutive years. Results: Plants on sandy and stony grasslands flowered and fruited throughout the year. We did not find a distinct seasonal pattern at the community level of either studied grassland. However, flowering, fruiting and seed dissemination occurred in stony grasslands mainly during the rainy season, while sandy grassland species flowered in both seasons and fruited and disseminated seed mainly during the dry season, as observed in other savanna vegetation types in the Cerrado. Flower and fruit production was higher in sandy grasslands than in stony grasslands, which may be linked to higher water retention in sandy grassland soils. In both communities, species of Cyperaceae, Eriocaulaceae and Xyridaceae contributed most to overall production, whereas Poaceae and Velloziaceae, two important families in campo rupestre, barely participated in the reproductive phenology during our 2-yr survey. Conclusions: Despite a strong seasonal climate, there was no reproductive seasonal pattern at the community level in campo rupestre. This first investigation of Neotropical grassland phenology indicates that the differences in soil content may constrain the grassland reproductive phenology and restrict reproduction of stony grassland species to the most favourable season. Further studies of grassland phenology are necessary to disentangle the relative importance of soil, climate and other triggers, especially fire.
Keywords: circular statistics; dissemination; flowering; fruiting; phenological strategy; rupestrian grassland; savanna; seasonality